Easy-to-process LDPE particles with high content of opening lubricant and preparation method thereof

By adding high content of open slip agent in LDPE and performing gamma irradiation treatment, the problems of poor fluidity and easy adhesiveness at high temperatures are solved, and better processing performance and product quality are achieved.

CN119775651APending Publication Date: 2025-04-08SHANGHAI TANGKE NEW PACKAGING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411976471.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

LDPE is prone to adhesion, poor fluidity and adhesive during high-temperature processing, which limits its application range and processing efficiency.

Method used

The easy-to-process LDPE particles with high content of open slip agent are used to control the amount of open slip agent, slip agent and ammonium polyphosphate, and the fluidity of LDPE is enhanced, and blended with EVA resin through gamma ray irradiation to reduce the crystallinity and viscosity of LDPE.

Benefits of technology

It significantly improves the fluidity and flexibility of LDPE, reduces the occurrence of adhesive phenomena, and improves processing performance and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220551370000101
    Figure BDA0005220551370000101
  • Figure BDA0005220551370000111
    Figure BDA0005220551370000111
Patent Text Reader

Abstract

The present application relates to the field of polymer materials, and specifically discloses an easy-to-process LDPE particle with a high content of an opening lubricant and a preparation method thereof. An easy-to-process LDPE particle with a high content of an opening lubricant comprises the following raw materials in parts by weight: 100 parts of LDPE resin, 0.2-0.3 parts of an opening lubricant, 0.3-0.4 parts of a lubricant and 5-7 parts of ammonium polyphosphate; the preparation method thereof is: LDPE resin, an opening lubricant, a lubricant and ammonium polyphosphate are uniformly mixed, melted, and extruded into granules. The easy-to-process LDPE particles of the present application have a large melt index, low viscosity, good fluidity during processing, are not easy to adhere to metals and produce agglomeration, and when made into plastic film products, have high mechanical strength and high transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and more specifically, to an easy-to-process LDPE particle with a high content of an opening lubricant and a preparation method thereof. Background Art

[0002] Polyethylene is a semi-crystalline thermoplastic resin made by polymerization reaction with ethylene as monomer. It has certain rigidity and flexibility, is odorless, non-toxic, has good chemical stability, low water absorption, and excellent electrical insulation. Polyethylene has many different classification methods according to the polymerization method, molecular weight, chain structure and performance. The more commonly used classification method is to classify according to the density of polyethylene resin, mainly including: high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE).

[0003] LDPE has a crystallinity of about 40% to 50% and a density of 0.91 to 0.925 g / cm 3 , melting point 105~110℃. The low crystallinity of LDPE structure improves the softness, extensibility, transparency, electrical insulation and processing performance of polyethylene. It can be used to prepare films, wires, cables, coatings, foamed plastics and other products, especially suitable for preparing soft and transparent plastic products. However, LDPE is prone to problems such as adhesion and poor fluidity during processing, especially under high temperature processing, which is prone to gelling, seriously affecting product quality and processing efficiency.

[0004] To this end, adding an open lubricant has become a common solution, but the amount of open lubricant added is generally low and it is difficult to meet high performance requirements. In the existing LDPE processing aid formula, the amount of open lubricant added is usually around 1000ppm and 500ppm, which improves the processing performance of LDEE to a certain extent, but under high processing temperature and high shear force conditions, the lubricant will decompose or migrate, causing the smoothness of the LDPE melt to seriously decline, so there are still problems such as insufficient fluidity and easy gelation, which limits the application range and processing efficiency of LDPE. Summary of the invention

[0005] In order to improve the fluidity of LDPE at high temperature and reduce its gelling phenomenon, the present application provides an easy-to-process LDPE particle with a high content of opening lubricant and a preparation method thereof.

[0006] In the first aspect, the present application provides an easy-to-process LDPE particle with a high content of opening lubricant, using the following technical solution: The invention discloses an easy-to-process LDPE particle with a high content of an opening lubricant, comprising the following raw materials in parts by weight: 100 parts of LDPE resin, 0.2-0.3 parts of an opening lubricant, 0.3-0.4 parts of a lubricant and 5-7 parts of ammonium polyphosphate.

[0007] By adopting the above technical scheme, the amount of the initial lubricant, lubricant and LDPE resin is controlled, the fluidity of the LDPE resin is enhanced, and the ammonium polyphosphate is attached to the surface of the metal to form a protective film, and the adhesion of the LDPE resin to the metal at high temperature is reduced, thereby reducing the gelling phenomenon.

[0008] Optionally, the LDPE resin is treated as follows: the LDPE resin is subjected to 60 Co The irradiation is carried out by gamma rays, the irradiation dose rate is (1-1.5) kGy / h, the total irradiation dose is 80-100 kGy, and then mixed with EVA resin in a mass ratio of 1:0.15-0.2, heated to 120-140°C, and granulated after banburying.

[0009] By adopting the above technical scheme, LDPE resin is subjected to irradiation, and a lower radiation dose rate is used, thereby inducing oxidative cracking of LDPE molecular chains, reducing intrinsic viscosity, and increasing fluidity. Moreover, the products with relatively low molecular weight generated after irradiation exist between LDPE macromolecular chains, which play a role in disentangling the molecular chains, thereby improving fluidity. EVA resin has reduced crystallinity and improved flexibility due to the presence of vinyl acetate monomer in the molecular chain. This flexibility makes it easier for EVA to interact and entangle with the molecular chains of LDPE during the mixing process, which is beneficial to improving the fluidity of the mixture. Moreover, there is a certain compatibility between EVA and LDPE, and the intermolecular interaction between the two can promote the dispersion and mixing of each other, thereby reducing energy consumption during the mixing process, improving mixing efficiency, improving the fluidity of LDPE, reducing the viscosity of the blending system, and making the mixture easier to flow and form during the processing process. Moreover, irradiation introduces oxygen-containing polar groups into the LDPE molecular chain, enhancing the interaction of molecular chain bonds, and γ-ray irradiation induces oxidative cracking of the LDPE molecular chain, resulting in an increase in crystallinity, so that the tensile strength of LDPE after irradiation increases.

[0010] Optionally, 3-5 parts by weight of a plasticizer, 10-15 parts by weight of a nucleating agent, and 0.1-0.15 parts by weight of a flow modifier are further added to the LDPE particles.

[0011] By adopting the above technical solution, the addition of plasticizer increases the lubrication effect between molecules and reduces the entanglement of molecular chains, thereby reducing the viscosity of the system, increasing the flow rate, improving the processing fluidity, being more conducive to processing, and reducing the occurrence of gelling. Nucleating agent can reduce the crystallization temperature of LDPE, induce LDPE molecular chains to form a crystalline structure faster during processing, make LDPE easier to crystallize and form a crystal nucleus, and refine the grains at the same time. The refinement of the grains means that more molecular chains can be arranged in an orderly manner in a smaller space, which helps to reduce the viscosity of LDPE, helps to shorten the crystallization time, reduces the interaction force between molecular chains, makes LDPE easier to flow in a molten state, improves production efficiency, improves melt index and fluidity, and at the same time, refines the grains to improve the transparency and surface gloss of the product and improve the mechanical properties of the product.

[0012] Optionally, the flow improver includes polystyrene-acrylamide copolymer coated mica powder and linear silicon-fluorine flow improver in a mass ratio of 1:0.1-0.2.

[0013] By adopting the above technical scheme, the polystyrene-acrylamide copolymer and mica powder can increase the free volume of the LDPE molecular chain bonds, increase the distance between molecules, reduce the interaction force, increase the activity of the molecular chain, and thus increase the melt index. In addition, the polystyrene-acrylamide copolymer and mica powder can also improve the tensile strength and bending modulus of LDPE, because when the LDPE composite material is subjected to external force, the polystyrene-acrylamide and mica powder in the composite material play a role in transferring stress, thereby playing a reinforcing role. The straight-chain silicon-fluorine flow modifier can greatly improve the dispersibility of the opening lubricant, and is distributed on the surface of the opening lubricant and the interface between the opening lubricant and the LDPE matrix, and the opening lubricant is coated in the LDPE mixed system to form a smooth coating, which effectively improves the dispersibility of the opening lubricant in LDPE, plays a role of internal lubrication, reduces the friction resistance between particles such as the opening lubricant and between the opening lubricant and the LDPE matrix, thereby improving processing fluidity; and when the LDPE composite material is subjected to external tension, the straight-chain silicon-fluorine flow modifier as a lubricating coating can effectively transfer the external force exerted on the LDPE matrix to the opening lubricant coated by the straight-chain silicon-fluorine flow modifier, so that the straight-chain silicon-fluorine flow modifier and the opening lubricant remain together in the deformation of the LDPE composite material, causing it to produce a large amount of yield deformation, and significantly improving the toughness of the composite system.

[0014] Optionally, the plasticizer includes POE, PEG-1000 and N-butylbenzenesulfonamide in a mass ratio of 5:1-2:2.5-3.

[0015] By adopting the above technical scheme, POE and LDPE have good compatibility in molecular structure, and their molecular weight distribution is narrow and they have good fluidity, so that POE can be used as a plasticizer modifier for LDPE to effectively improve the performance of LDPE, increase toughness and processing performance, and POE has an amorphous structure and good molecular chain activity. After blending with LDPE, POE can reduce the crystallinity of LDPE, increase the proportion of amorphous regions, improve its fluidity, and increase its melt index; PEG-1000 and N-butylbenzenesulfonamide play a lubricating role, increase the lubrication degree between molecules in the blending system, enhance the movement of molecules, reduce the entanglement density between molecules, improve the fluidity of the blending system, reduce the viscosity of the blending system, and increase the melt flow rate, which is more conducive to processing, and reduces the van der Waals force between molecules, and makes the force between dispersed phase systems more stable, thereby improving impact strength.

[0016] Optionally, the nucleating agent is oleylamine-modified CBC resin filled with mesoporous silica.

[0017] By adopting the above technical solution, the surface of silica contains hydroxyl groups, which can react chemically with functional groups such as amino or carboxyl groups in oleylamine molecules, so that the oleylamine molecules are grafted onto the surface of silica, and the dispersibility of silica in LDPE is improved, which helps to evenly distribute silica, increase compatibility with LDPE, reduce interface defects, and improve the mechanical strength of LDPE materials; and the silica used as a nucleating agent can promote the reaction of LDPE, promote the formation of LDPE and increase the number of its crystal nuclei, reduce the crystallization temperature, make the arrangement of LDPE molecular chains in the molten state looser, reduce the melt viscosity, improve the fluidity, and accelerate the crystallization process, shrink Short crystallization time; CBC resin is polyvinylcyclohexane-b-polyethylene-b-polyvinylcyclohexane (PVCH-PE-PVCH), which is a crystalline-non-crystalline triblock polymer. CBC has a unique structure and properties, making it a potential polymer material. CBC has excellent thermal stability, durability and chemical stability, very high transparency, high fluidity, excellent UV stability and low water absorption. Filling mesoporous silica with CBC resin can reduce the porosity of mesoporous silica, thereby reducing light scattering and refraction, improving the light transmittance of mesoporous silica, and thereby increasing the transparency of LDPE products.

[0018] Optionally, the preparation method of the oleylamine-modified CBC resin filled mesoporous silica is as follows: The CBC resin is mixed with a hydrogen peroxide solution having a concentration of 3-6 wt%, ultrasonicated for 10-15 min, filtered, washed and then dried to obtain an oxidized CBC resin; The oxidized CBC resin is mixed with chloroform, and stirred and dissolved at 70-80°C to obtain a treatment solution with a concentration of 4.5-5wt%; the mesoporous silica is immersed in the treatment solution, and the pressure is maintained at -(0.02-0.06)MPa for 20-30min and the pressure is released for 10-20min, and the cycle is repeated 3-5 times, and then filtered and dried to obtain CBC resin-filled mesoporous silica; The CBC resin-filled mesoporous silica and oleylamine are mixed, anhydrous ethanol is added to prepare a suspension, which is centrifuged, washed with anhydrous ethanol, and dried.

[0019] By adopting the above technical scheme, CBC resin is oxidized by hydrogen peroxide, so that unsaturated bonds such as certain carbon-hydrogen bonds in the polyethylene ring or polyethylene segment are oxidized to carboxyl groups, thereby obtaining oxidized CBC resin, dissolving the oxidized CBC resin to prepare a treatment liquid, and filling the treatment liquid into the pores of mesoporous silica by negative pressure, thereby reducing the scattering and refraction of light by the pores of the mesoporous silica, enhancing the light transmittance, and improving the transparency. At the same time, the mesoporous silica filled with the oxidized CBC resin solution, not only the hydroxyl groups on the surface of the silica can be grafted with the amino groups of oleylamine, but also the carboxyl groups contained in the oxidized CBC resin can react with the amino groups of oleylamine, thereby increasing the grafting amount of oleylamine and enhancing the lipophilicity of the mesoporous silica, thereby further improving its dispersibility in LDPE.

[0020] Optionally, the particle size of the mesoporous silica is 5-9 μm.

[0021] By adopting the above technical scheme, the size uniformity of the mesoporous silica within the particle size is good, the monodispersity of the particles and the smoothness of the surface of the nano-microspheres are good, and the good dispersibility is conducive to the grafting modification of oleylamine.

[0022] Optionally, the opening lubricant is selected from at least one of silicon dioxide, calcium carbonate, clay, talc and pottery clay; The lubricant is selected from at least one of oleamide, erucamide, zinc stearate, magnesium stearate and calcium stearate.

[0023] In a second aspect, the present application provides a method for preparing easy-to-process LDPE particles with a high content of opening lubricant, using the following technical solution: A method for preparing easy-to-process LDPE particles with a high content of open lubricant comprises the following steps: uniformly mixing LDPE resin, open lubricant, lubricant and ammonium polyphosphate, plasticizer, nucleating agent and flow modifier, melting and extruding to granulate.

[0024] By adopting the above technical solution, LDPE particles can be obtained by mixing and extruding the raw materials. The preparation method is simple and easy to operate.

[0025] In summary, this application has the following beneficial effects: 1. Since the present application uses an appropriate amount of open lubricant, lubricant and ammonium polyphosphate as additives to reduce the gelling property of LDPE, the open lubricant and lubricant can increase the fluidity of LDPE and reduce the viscosity, while ammonium polyphosphate can adhere to the metal surface and form a protective film, thereby reducing the adhesion of LDPE on the metal surface and avoiding gelling.

[0026] 2. In the present application, gamma ray irradiation and EVA resin are preferably used to pretreat the LDPE resin to increase the fluidity and flexibility of the LDPE resin and reduce the viscosity of the blending system; POE, PEG-1000 and N-butylbenzenesulfonamide are also used as plasticizers, which can effectively increase the toughness and processing type of LDPE, while improving its fluidity and enhancing impact strength; in addition, a blend of polystyrene-acrylamide copolymer-coated mica powder and a linear silicon-fluorine flow improver is used as a flow modifier, and the polystyrene-acrylamide copolymer and mica powder can also improve the tensile strength and flexural modulus of LDPE, and increase the molecular chain activity and melt index, while the linear silicon-fluorine flow improver can form a smooth coating at the interface of the opening lubricant and LDPE, thereby playing an internal lubricating role, reducing the friction resistance during flow, further improving the melt index, and preventing the formation of gumming.

[0027] 3. In the present application, it is also preferred to use oleylamine-modified CBC resin to fill mesoporous silica, oxidize the CBC resin with hydrogen peroxide to make it contain carboxyl groups, and use the oxidized CBC resin to fill the agglomerated silica to reduce its porosity, reduce the refraction and reflection of light, and the hydroxyl groups contained on the surface of the mesoporous silica and the carboxyl groups in the oxidized CBC resin can react with the amino groups in oleylamine, thereby improving the lipophilicity of the mesoporous silica, improving its dispersibility and compatibility in LDPE, reducing agglomeration, and increasing mechanical strength and transparency. DETAILED DESCRIPTION

[0028] The following examples further illustrate the present application in detail.

[0029] Preparation Example 1-5 of Mesoporous Silica Filled with Oleylamine-Modified CBC Resin The weight average molecular weight of the CBC resin (polyvinylcyclohexane-b-polyethylene-b-polyvinylcyclohexane (PVCH-b-PE-b-PVCH)) in Preparation Example 1 is 5.5×10 4 , where the Mw of PVCH is 2×10 4 , the Mw of PE is 1.375×10 4 The particle size of mesoporous silica is 5-9 μm, selected from Wuhu Xinda New Materials Technology, model XD-S05J, and the pore diameter is 5-20 nm.

[0030] Preparation Example 1: (1) CBC resin was mixed with a 3 wt % hydrogen peroxide solution, ultrasonicated at 250 W for 15 min, filtered, washed with deionized water, and dried at 70° C. for 8 h to obtain an oxidized CBC resin; (2) 5 g of oxidized CBC resin was mixed with chloroform and stirred at 70° C. until the mixture was completely dissolved to prepare a treatment solution having a concentration of 4.5 wt %; (3) 10 g of mesoporous silica was immersed in the treatment solution, maintained at -0.06 MPa for 20 min and then released for 10 min, and the negative pressure and pressure release were cycled for 5 times, filtered, and dried at 80° C. to obtain CBC resin-filled mesoporous silica; (4) 1 g of CBC resin-filled mesoporous silica and 7.4 ml of oleylamine were mixed, and 20 ml of anhydrous ethanol at a temperature of 45° C. was added to prepare a suspension. The suspension was centrifuged at a speed of 6000 r / min for 15 min. The precipitate was washed five times with 15 ml of anhydrous ethanol at a temperature of 45° C., and the ethanol was dried at 75° C.

[0031] Preparation Example 2: (1) CBC resin was mixed with a 6 wt % hydrogen peroxide solution, ultrasonicated at 250 W for 10 min, filtered, washed with deionized water, and dried at 70° C. for 8 h to obtain an oxidized CBC resin; (2) 5 g of oxidized CBC resin was mixed with chloroform and stirred at 80° C. until the mixture was completely dissolved to prepare a treatment solution having a concentration of 5 wt %; (3) 10 g of mesoporous silica was immersed in the treatment solution, maintained at -0.02 MPa for 30 min and then released for 20 min, and the negative pressure and pressure release were cycled for 3 times, filtered, and dried at 80° C. to obtain CBC resin-filled mesoporous silica; (4) 1 g of CBC resin-filled mesoporous silica and 7.4 ml of oleylamine were mixed, and 20 ml of anhydrous ethanol at a temperature of 45° C. was added to prepare a suspension. The suspension was centrifuged at a speed of 6000 r / min for 15 min. The precipitate was washed five times with 15 ml of anhydrous ethanol at a temperature of 45° C., and the ethanol was dried at 75° C.

[0032] Preparation Example 3: The difference from Preparation Example 1 is that the CBC resin is not subjected to oxidation treatment. 5 g of CBC resin is mixed with chloroform and stirred at 80° C. until completely dissolved to obtain a treatment solution with a concentration of 5 wt %. The remaining steps are the same as those in Preparation Example 1.

[0033] Preparation Example 4: The difference from Preparation Example 1 is that oxidized CBC resin is not used to fill the mesoporous silica, 10 g of mesoporous silica is mixed with 7.4 ml of oleylamine, 20 ml of anhydrous ethanol at 45°C is added to obtain a suspension, the suspension is centrifuged at 6000 r / min for 15 min, the precipitate is washed 5 times with 15 ml of anhydrous ethanol at 45°C, and the ethanol is dried at 75°C.

[0034] Preparation Example 5: The difference from Preparation Example 1 is that oleylamine is not used to modify the CBC resin-filled mesoporous silica, and the CBC resin-filled mesoporous silica is used as a nucleating agent.

[0035] Preparation Example 6 of polystyrene-acrylamide copolymer coated mica powder: 87.5g of styrene, 5.2g of acrylamide, 5.2g of initiator AIBN, and 100ml of THF were mixed, the temperature was raised to 80°C with stirring, and the mixture was kept warm for 2h. The reaction solution was poured into 1000ml of methanol for precipitation, and the process was repeated 3 times. The mixture was vacuum dried at 80°C to obtain a polystyrene-acrylamide copolymer. The polystyrene-acrylamide copolymer and mica powder were mixed in a mass ratio of 1.5:1, and the mixture was extruded and granulated at 195°C.

[0036] Preparation Example 7 of a linear silicon-fluorine flow improver: 17.2 g of silicone oil, 4.88 g of 4-hydroxybenzaldehyde and 100 ml of ethanol were mixed, nitrogen was introduced, the temperature was raised to 50° C., the reaction was performed for 4 h, 8.64 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, the reaction was performed at room temperature for 12 h, the solvent was removed by rotary evaporation, and vacuum dried at 70° C. to obtain an intermediate; 7.5 g of the intermediate and 1.9 g of p-trifluoromethylbenzoic acid were added to a container containing 50 ml of dichloromethane, and a mixed solution prepared by 2.06 g of N, N-dicyclohexylcarbodiimide, 0.282 g of 4-dimethylaminopyridine and 10 ml of dichloromethane was added. The mixture was subjected to esterification reaction at 30°C for 24 h, filtered, and the filtrate was washed three times with 10% sodium carbonate solution and sodium chloride solution. The solvent was removed by rotary evaporation and vacuum dried at 70°C for 12 h. Example

[0037] Example 1: An easy-to-process LDPE granule with a high content of opening lubricant. The raw material dosage is shown in Table 1, wherein the melt index (190°C, 2.16kg) of the LDPE resin is 15g / 10min, and the density is 0.92g / cm 3 , selected from Saudi Sabic, model 2015T, the opening lubricant is silicon dioxide, and the lubricant is erucamide.

[0038] The preparation method of the above-mentioned easy-to-process LDPE particles with a high content of opening lubricant is as follows: The LDPE resin, the opening lubricant, the lubricant and the ammonium polyphosphate are mixed evenly, melted and extruded into granules. The extrusion temperatures are 200°C for the first zone, 230°C for the second zone, 245°C for the third zone, 250°C for the fourth zone and 250°C for the fifth zone.

[0039] Table 1 Raw material dosage of easy-to-process LDPE particles in Examples 1-3 and 8-9 Raw material / g Example 1 Example 2 Example 3 Example 8 Example 9 LDPE resin 100 100 100 100 100 Opening lubricant 0.2 0.3 0.2 0.2 0.2 Lubricant 0.3 0.4 0.3 0.3 0.3 Ammonium Polyphosphate 0.5 0.7 0.6 0.5 0.5 Plasticizers 0 0 0 5 3 Nucleating Agent 0 0 0 15 10 Flow Improvers 0 0 0 0.15 0.1 Example 2: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 1 is that the raw material dosage is as shown in Table 1, wherein the melt index (190°C, 2.16kg) of LDPE is 20g / 10min, selected from Singapore, model MBW0722, the opening lubricant is calcium carbonate, and the lubricant is zinc stearate.

[0040] Example 3: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 1 is that the raw material dosage is as shown in Table 1, wherein the melt index (190°C, 2.16kg) of LDPE is 2.8g / 10min, and the density is 0.925g / cm 3 , selected from Shanghai Petrochemical, model Q281, the opening lubricant is talcum powder, and the lubricant is oleic acid amide.

[0041] Example 4: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 1 in that the LDPE resin is pretreated as follows: LDPE resin was treated with 60 Co The irradiation was carried out by gamma ray, the irradiation dose rate was 1 kGy / h, the total irradiation dose was 100 kGy, the irradiated LDPE resin and EVA resin were mixed in a mass ratio of 1:0.2, the temperature was raised to 140°C, and granulation was performed after banburying for 10 minutes. The EVA resin was selected from Mitsui Chemicals of Japan, the model was 40W, the melt index (190°C, 2.16 kg) was 65 g / 10 min, and the density was 0.965 g / cm 3 , VA content is 40%.

[0042] Example 5: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 1 in that the LDPE resin is pretreated as follows: LDPE resin was treated with 60 Co The irradiation was carried out by gamma ray, the irradiation dose rate was 1.5 kGy / h, the total irradiation dose was 80 kGy, the irradiated LDPE resin and EVA resin were mixed in a mass ratio of 1:0.15, the temperature was raised to 130 ° C, and granulated after banburying for 10 minutes. The EVA resin was selected from Mitsui Chemicals of Japan, the model was 40W, the melt index (190 ° C, 2.16 kg) was 65 g / 10 min, and the density was 0.965 g / cm3 , VA content is 40%.

[0043] Example 6: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 4 in that the LDPE resin is pretreated as follows: LDPE resin was treated with 60 Co Gamma rays were used for irradiation, with an irradiation dose rate of 1 kGy / h and a total irradiation dose of 100 kGy.

[0044] Example 7: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 4 in that the LDPE resin is pretreated as follows: LDPE resin and EVA resin were mixed in a mass ratio of 1:0.2, heated to 140°C, and granulated after 10 minutes of banburying. The EVA resin was selected from Mitsui Chemicals of Japan, model 40W, melt index (190°C, 2.16kg) of 65g / 10min, and density of 0.965g / cm 3 , VA content is 40%.

[0045] Example 8-9: An easy-to-process LDPE particle with a high content of open lubricant, which is different from Example 4 in that a plasticizer, a nucleating agent and a flow modifier are also added. The raw material dosage is shown in Table 1. The nucleating agent is mesoporous silica with a particle size of 5-9 μm, selected from Wuhu Xinda New Material Technology, model XD-S05J, and a pore diameter of 5-20 nm. The plasticizer includes POE, PEG-1000 and N-butylbenzenesulfonamide in a mass ratio of 5:2:3. The melt index of POE is 30 g / 10 min and the density is 1.3 g / cm 3 , selected from LG of South Korea, with the brand name LC168, the flow improver includes polystyrene-acrylamide copolymer-coated mica powder and linear silicon-fluorine flow improver in a mass ratio of 1:0.2, the polystyrene-acrylamide copolymer-coated mica powder is prepared from Preparation Example 6, and the linear silicon-fluorine flow improver is prepared from Preparation Example 7; the preparation method of the easy-to-process LDPE with a high content of opening lubricant is as follows: LDPE resin, opening lubricant, lubricant and ammonium polyphosphate, plasticizer, nucleating agent and flow improver are uniformly mixed, melted, extruded and granulated, and the extrusion temperature is 200°C in zone one, 230°C in zone two, 245°C in zone three, 250°C in zone four, and 250°C in zone five.

[0046] Example 9: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 4 in that a plasticizer, a nucleating agent and a flow modifier are further added. The raw material dosage is shown in Table 1. The nucleating agent is mesoporous silica with a particle size of 5-9 μm, selected from Wuhu Xinda New Material Technology, model XD-S05J, and a pore diameter of 5-20 nm. The plasticizer includes POE, PEG-1000 and N-butylbenzenesulfonamide in a mass ratio of 5:2:3. The melt index of POE is 30 g / 10 min and the density is 1.3 g / cm 3 , selected from LG of South Korea, with the brand name LC168, the flow improver includes polystyrene-acrylamide copolymer-coated mica powder and linear silicon-fluorine flow improver in a mass ratio of 1:0.1, the polystyrene-acrylamide copolymer-coated mica powder is prepared from Preparation Example 6, and the linear silicon-fluorine flow improver is prepared from Preparation Example 7; the preparation method of the easy-to-process LDPE with a high content of opening lubricant is as follows: LDPE resin, opening lubricant, lubricant and ammonium polyphosphate, plasticizer, nucleating agent and flow improver are mixed evenly, melted, extruded and granulated, and the extrusion temperature is 200°C in zone one, 230°C in zone two, 245°C in zone three, 250°C in zone four, and 250°C in zone five.

[0047] Example 10: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 9 in that no polystyrene-acrylamide copolymer-coated mica powder is added to the flow modifier.

[0048] Example 11: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 9 in that the polystyrene-acrylamide copolymer-coated mica powder is used in the flow improver to replace the linear silicon-fluorine flow improver in an equal amount.

[0049] Example 12: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 9 in that the plasticizer is polyethylene wax.

[0050] Example 13: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 9 is that the nucleating agent is oleylamine-modified CBC resin-filled porous silica, and the oleylamine-modified CBC resin-filled porous silica is prepared by Preparation Example 1.

[0051] Example 14: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 9 is that the nucleating agent is oleylamine-modified CBC resin-filled porous silica, and the oleylamine-modified CBC resin-filled porous silica is prepared by Preparation Example 2.

[0052] Example 15: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 13 is that the nucleating agent is oleylamine-modified CBC resin-filled porous silica, and the oleylamine-modified CBC resin-filled porous silica is prepared by Preparation Example 3.

[0053] Example 16: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 13 is that the nucleating agent is oleylamine-modified CBC resin-filled porous silica, and the oleylamine-modified CBC resin-filled porous silica is prepared by Preparation Example 4.

[0054] Example 17: An easy-to-process LDPE particle with a high content of opening lubricant. The difference from Example 13 is that the nucleating agent is oleylamine-modified CBC resin-filled porous silica, and the oleylamine-modified CBC resin-filled porous silica is prepared by Preparation Example 5.

[0055] Comparative Example Comparative Example 1: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 1 in that the addition amount of the opening lubricant is 0.1 g.

[0056] Comparative Example 2: An easy-to-process LDPE particle with a high content of opening lubricant, which is different from Example 1 in that the addition amount of the opening lubricant is 0.05 g.

[0057] Performance testing LDPE particles were prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 2.

[0058] 1. Melt index: Use a melt index tester to measure the melt index of the composite material under certain conditions (set temperature: 190°C, weight: 2.16 kg).

[0059] 2. Tensile strength: Tested according to GB / T1040.2-2006 "Determination of tensile properties of plastics", the tensile speed is 10mm / min, and the sample type is 1A.

[0060] 3. Impact strength: Test in accordance with GB / T1843-1996 "Hard Plastic Cantilever Beam Impact Test Method".

[0061] 4. Light transmittance: LDPE particles and antioxidant 1010 were mixed in a mass ratio of 95:5, melt-extruded and stretched to prepare a film. During extrusion, the temperature settings of each zone of the screw extruder were as follows: Zone I temperature: 150°C, Zone II temperature: 210°C, Zone III temperature: 200°C, Zone IV temperature: 200°C, Zone V temperature: 190°C, and die head temperature: 190°C; the main speed of the extruder was 60r / min, the film width was 190mm, the blowing ratio was 2.0, the stretching speed was 5m / min, the film thickness was controlled to be 30±3μm, the screw diameter of the film blowing machine extruder was L / D=25:1, and the die diameter was 50mm; and then the light transmittance was tested in accordance with GBT 2410-2008 "Standard for Determination of Light Transmittance and Haze of Transparent Plastics".

[0062] Table 2 Performance test of easy-to-process LDPE particles Combining the test data in Examples 1-3 and Table 2, it can be seen that by using LDPE with different melt indexes as raw materials and controlling the appropriate proportion of the opening lubricant and the lubricant, the melt index of the prepared LDPE particles is significantly increased. It can be seen that appropriately increasing the amount of the opening lubricant and the lubricant can effectively improve the flow coefficient of the LDPE particles, reduce its viscosity, and reduce the possibility of gelling of the overall material.

[0063] Compared with Example 1, in Examples 4 and 5, the LDPE resin is first irradiated with gamma rays and then blended with the EVA resin. It can be seen that the fluidity of the LDPE particles prepared in Examples 4 and 5 is increased, and the tensile strength and light transmittance are further improved.

[0064] Compared with Example 4, Examples 6 and 7 respectively only use γ-ray irradiation and EVA resin blending. It can be seen that the melt index of the LDPE particles in Example 6 is reduced, the fluidity is reduced, but the tensile strength is increased, while the flow coefficient of the LDPE particles in Example 7 is reduced, but the tensile strength is increased, and the transparency is improved, indicating that pretreatment of LDPE resin with γ-rays and EVA resin can not only improve its melt index and increase its fluidity, but also enhance its mechanical properties and transparency.

[0065] Compared with Example 4, Examples 8 and 9 further add plasticizers, nucleating agents and flow modifiers to the LDPE particles, using POE, PEG-100 and N-butylbenzenesulfonamide as plasticizers, polystyrene-acrylamide copolymer-coated mica powder and linear silicon-fluorine flow improvers as flow modifiers, and mesoporous silica as a nucleating agent. It can be seen that the LDPE materials prepared in Examples 8 and 9 and the LDPE particles prepared in Examples 8 and 9 have increased melt index and improved fluidity, which further reduces the possibility of gelling, and also have enhanced toughness and improved light transmittance.

[0066] Compared with Example 9, Example 10 does not add polystyrene-acrylamide copolymer-coated mica powder. The data in Table 2 show that the fluidity of the LDPE particles prepared in Example 10 is reduced, but the light transmittance thereof is slightly improved. In Example 11, polystyrene-acrylamide copolymer-coated mica powder is used to replace the linear silicon-fluorine flow improver. The fluidity of the LDPE particles prepared in Example 11 does not change much, but the transparency of the plastic film prepared therefrom is significantly reduced.

[0067] Compared with Example 9, polyethylene wax is used as a plasticizer in Example 12. It can be seen that the melt index of the LDPE particles prepared in Example 12 decreases, and the tensile strength and impact strength decrease.

[0068] Compared with Example 9, Example 13 and Example 14 use the oleylamine-modified CBC resin prepared in Preparation Example 1 and Preparation Example 2 to fill mesoporous silica. Table 2 shows that the melt index of the LDPE particles prepared in Example 13 and Example 14 is further improved, and the toughness is enhanced and the mechanical strength is improved.

[0069] In Example 15, the oleylamine-modified CBC resin prepared in Preparation Example 3 was used to fill mesoporous silica. Compared with Preparation Example 1, the CBC resin was not oxidized. The melt index and transparency of the LDPE particles prepared in Example 15 were not as good as those in Example 13.

[0070] In Example 16, compared with Example 13, the oleylamine-modified CBC resin prepared in Preparation Example 4 was used to fill mesoporous silica, wherein the mesoporous silica was not filled with oxidized CBC resin, and only oleylamine was used to modify the mesoporous silica. It can be seen that the melt index of the LDPE particles is reduced and the transparency is decreased.

[0071] In Example 17, the oleylamine-modified CBC resin prepared in Preparation Example 5 was used to fill the mesoporous silica, without using oleylamine for modification, and only the CBC resin was used to fill the mesoporous silica. Compared with Example 13, the transparency did not change much, but the fluidity decreased.

[0072] Compared with Example 1, Comparative Examples 1 and 2 increase and decrease the amount of the opening lubricant added, respectively. From the comparison of the data in Table 2, it can be seen that the melt index of the LDPE particles prepared in Comparative Examples 1 and 2 is significantly reduced, and the fluidity becomes worse.

[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An easy-to-process LDPE granule with a high content of opening lubricant, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of LDPE resin, 0.2-0.3 parts of opening lubricant, 0.3-0.4 parts of lubricant and 5-7 parts of ammonium polyphosphate.

2. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 1, characterized in that: The LDPE resin is treated as follows: the LDPE resin is subjected to 60 Co The irradiation is carried out by gamma rays, the irradiation dose rate is (1-1.5) kGy / h, the total irradiation dose is 80-100 kGy, and then mixed with EVA resin in a mass ratio of 1:0.15-0.2, heated to 120-140°C, and granulated after internal mixing.

3. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 1, characterized in that: The LDPE particles are further added with 3-5 parts by weight of a plasticizer, 10-15 parts by weight of a nucleating agent, and 0.1-0.15 parts by weight of a flow modifier.

4. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 3, characterized in that: The flow improver comprises polystyrene-acrylamide copolymer coated mica powder and a linear silicon-fluorine flow improver in a mass ratio of 1:0.1-0.

2.

5. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 3, characterized in that: The plasticizer includes POE, PEG-1000 and N-butylbenzenesulfonamide in a mass ratio of 5:1-2:2.5-3.

6. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 3, characterized in that: The nucleating agent is oleylamine-modified CBC resin filled with mesoporous silica.

7. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 6, characterized in that: The preparation method of the oleylamine-modified CBC resin filled mesoporous silica is as follows: The CBC resin is mixed with a hydrogen peroxide solution having a concentration of 3-6 wt%, ultrasonicated for 10-15 min, filtered, washed and dried to obtain an oxidized CBC resin; Mix the oxidized CBC resin with chloroform, stir and dissolve at 70-80°C to prepare a treatment solution with a concentration of 4.5-5wt%; The mesoporous silica is immersed in the treatment liquid, and the pressure is maintained at - (0.02 ~ 0.06) MPa for 20-30 minutes and the pressure is released for 10-20 minutes, and the cycle is repeated 3-5 times, and then filtered and dried to obtain CBC resin filled mesoporous silica; The CBC resin-filled mesoporous silica and oleylamine are mixed, anhydrous ethanol is added to prepare a suspension, which is centrifuged, washed with anhydrous ethanol, and dried.

8. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 6, characterized in that: The particle size of the mesoporous silica is 5-9 μm.

9. The easy-to-process LDPE particles with a high content of opening lubricant according to claim 1, characterized in that: The opening lubricant is selected from at least one of silicon dioxide, calcium carbonate, clay, talcum powder and pottery clay; The lubricant is selected from at least one of oleamide, erucamide, zinc stearate, magnesium stearate and calcium stearate.

10. The method for preparing the easy-to-process LDPE particles with a high content of opening lubricant according to any one of claims 1 to 9, characterized in that: The following steps are involved: The LDPE resin, the opening lubricant, the lubricant and the ammonium polyphosphate, the plasticizer, the nucleating agent and the flow modifier are uniformly mixed, melted and extruded into granules.

Citation Information

Cited By

  • Medicinal chlorinated butyl rubber sealing ring and preparation method thereof

    CN121045697A